HYPOTONICITY INDUCED HUMAN RED BLOOD CELL (HRBC) MEMBRANE STABILIZATION POTENTIAL OF CRUDE ETHANOLIC EXTRACT OF CINNAMOMUM VERUM - Anushya, P.; R, Gayathri; Priya, V.Vishnu (International Journal of Psychosocial Rehabilitation, 2020)
Cinnamomum verum may be a common species. It cures respiratory disease, digestive discomfort and gynaecological syndrome. Inflammation may be a biological response of the system to harmful stimuli and it’s characterised by redness, swelling, pain and loss of tissue function. Now -a -days NSAIDS is employed widely to stop inflammation. But it has more side effects. Due to this side effect, it’s necessary to seek out a natural anti-inflammatory agent. to work out the anti-inflammatory activity in crude Ethanolic extract of Cinnamomum verum . Cinnamon verum was purchased from herbal cure centre . Ethanolic extract of Cinnamon verum was prepared and its anti-inflammatory activity was evaluated by hypotonicity induced HRBC membrane stabilization.: As observed from the study, we can conclude that cinnamomum verum has anti-inflammatory activity. Cinnamomum verum exhibits anti-inflammatory activity by stabilizing the lysosomal membrane.